Aragorn: Eliciting and Maintaining Secure Service Policies. - Ajmeri, Nirav; Hang, Chung-Wei; Parsons, Simon D.; Singh, Munindar P. (Computer (00189162), 2017)
Services are configured via policies that capture expected behaviors, but stakeholder requirements can change, making policy errors a surprisingly common occurrence. Aragorn applies formal argumentation to produce policies that balance stakeholder concerns.